1986
DOI: 10.1029/ja091ia07p08011
|View full text |Cite
|
Sign up to set email alerts
|

Radar studies of long‐wavelength waves associated with mid‐latitude sporadic E layers

Abstract: The Cornell University Portable Radar Interferometer (CUPRI), a 50-MHz Doppler radar system, was operated during May and August/September 1983 on the island of St. Croix (17.7øN, 64.8øW) to study the plasma instabilities associated with nighttime sporadic E layers. Two events, on May 7 and August 22, show evidence of large-amplitude waves, with apparent horizontal wavelengths of 10-12 km and periods of 2-6 min. These apparent wavelengths are upper limits for the true wavelengths. The CUPRI beam was directed ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
100
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(113 citation statements)
references
References 30 publications
13
100
0
Order By: Relevance
“…1, the echo intensity variations are followed rather closely, although not always in phase, by a wavelike variation in Doppler velocity. Actually, the velocity fluctuates mostly between ± 100 m/s, in good agreement with similar 50-MHz observations reported before by Ecklund et al (1981) and Riggin et al (1986). Figure 1 shows that the observed spectra are basically type 2, that is , rather broad with their mean (or peak) Doppler velocities near and around zero Doppler shift.…”
Section: The Experimentssupporting
confidence: 79%
“…1, the echo intensity variations are followed rather closely, although not always in phase, by a wavelike variation in Doppler velocity. Actually, the velocity fluctuates mostly between ± 100 m/s, in good agreement with similar 50-MHz observations reported before by Ecklund et al (1981) and Riggin et al (1986). Figure 1 shows that the observed spectra are basically type 2, that is , rather broad with their mean (or peak) Doppler velocities near and around zero Doppler shift.…”
Section: The Experimentssupporting
confidence: 79%
“…Mid-latitude sporadic-E scattering is regularly observed by HF and VHF radars during summer at night (Goodwin, 1965;Ecklund et al, 1981;Tanaka and Venkateswaran, 1982a, b;Keys and Andrews, 1984;Riggin et al, 1986;Fukao et al, 1991;Yamamoto et al, 1991Yamamoto et al, , 1992Yamamoto et al, , 1994Haldoupis and Schlegel, 1993;Bourdillon et al, 1995); nevertheless, this phenomenon is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…The real situation can be more complicated in irregular layers, for instance in partially re¯ecting layers and in spread Es (From and Whitehead, 1986) inside which one can expect that non-vertical density gradients also exist. VHF and HF radar observations revealed that the scattering layer is very often a ected by spatial modulation of the backscattered power and also of the Doppler shift and width (Riggin et al, 1986;Fukao et al, 1991;Yamamoto et al, 1991Yamamoto et al, , 1992Yamamoto et al, , 1994Bourdillon et al, 1995). Riggin et al (1986) attributed their observed large-scale structures and the associated high velocities, sometimes exceeding 250 m/s, to kilometer-scale plasma waves generated by the gradient drift instability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been a surprise at first because it had long been thought that the only places with the right combination of electric fields and density gradients were the equatorial electrojet region with its combination of strong currents and ambient density gradients and the auroral regions with their very strong ambient electric fields. However, following their initial discovery at mid latitudes, in association with sporadic E layers, (Tanaka & Venkateswaran, 1982;Ecklund et al, 1981;Riggin et al, 1986) it has become clear that E-region echoes have a rich morphology even at mid and low latitudes, as witnessed by so-called quasiperiodic (QP) echo patterns (Yamamoto et al, 1991;Choudhary & Mahajan, 1999;Chau & Woodman, 1999). In fact, while the association with sporadic E layers seems clear, it is interesting to note that some of the echoes at mid latitudes have Doppler shifts of the order of a few 100 m/s, which is clearly larger than any ambient electric field could provide (Haldoupis et al, 1997).…”
Section: Introductionmentioning
confidence: 99%